SUPLEMENTASI DOCOSAHEXAENOIC ACID (DHA) SEBAGAI USAHA PREVENTIF IBU HAMIL DENGAN RISIKO PREEKLAMPSIA - Clara Asifa; Rodiani Rodiani (Jurnal Kesehatan, 2021)
Hypertension in pregnancy is one of the main cause of maternal death in the world. Hypertensive disorders in pregnancy, including preeclampsia, have a broad spectrum of conditions associated with maternal and fetal morbidity and mortality. Preeclampsia is a syndrome characterized by new onset of hypertension at ≥20 weeks of gestation, in pregnant women who were previously normotensive and accompanied by proteinuria. This paper aims to determine the effectiveness of docosahexaenoic acid (DHA) in pregnant women to prevent the risk of preeclampsia. This research method is to review the articles published in the last 10 years with the keywords preeclampsia, therapy, preventive, and docosahexaenoic acid (DHA). The data show that administration of docosahexaenoic acid (DHA) can reduce the risk of preeclampsia with minimal side effects for both maternal and the fetus. DHA on the other hand is still insignificant in preventing preeclampsia in high-risk pregnant women and prescribing the high dose of DHA is not recommended for pregnant women. DHA will be more effective in preventing preeclampsia if given in early pregnancy, especially in the first trimester of pregnancy